Synthesis and pot trial of organic fertilizer from solid waste - Purnomo, C. W.; Noviyani, P.; Indarti, S.; Schriefer, G. T. (2022)
Organic farming nowadays is becoming popular and getting high attention worldwide. This growing field needs many nutrient sources from natural resources since organic farming cannot use synthetic fertilizer. Thus, many sources of nutrient-rich solids are being used to fulfill the demand. Here, chicken feather powder, horn powder, poultry manure, and compost are used for producing organic fertilizer. These solid waste materials are blended in various compositions, i.e., horn plus poultry and horn plus compost. Selected fertilizer formulations were tested to grow barley in a pot trial inside a glasshouse using several dosages. After about four weeks old, the barley plant is harvested and weighed to determine the optimum fertilizer formula and dosage. It appears that fertilizer formula using horn and poultry is the best fertilizer that can produce the highest biomass in a respective time and compete with synthetic NPK fertilizer. © 2022 Institute of Physics Publishing. All rights reserved.